Perspektif Ulama NU Dan Ulama PERSIS Garut Tentang Adu Seni Ketangkasan Domba Garut - Sunarsa, Sasa; Nur Azizah, Sopiyanti (STAI Al Musaddadiyah Garut, 2024)
The Garut art of sheep fighting is a typical cultural tradition from Garut, West Java, Indonesia, which involves a fight between two rams. This tradition is not just a physical fight between animals, but is also a manifestation of local art and cultural heritage which is appreciated and maintained by the local community. However, among the public, especially according to the views of NU Ulama and Persis Ulama, the art of fighting against each other is still controversial to this day. The problem formulation in this research is: 1). What is the mechanism for sheep dexterity competitions? 2). What is the perspective of the NU Ulama and Persis Garut Ulama regarding the Garutsheep dexterity competition? The aim of this research is to find out the mechanism of sheep agility contests as well as the perspective of Ulama Nu and UlamaPersis Garut regarding Garut sheep agility contests. The method used by the author is field research, and this research also uses descriptive methods and analysis with a qualitative approach. The results of the research can be concluded that from the mechanism and perspective of Nu Ulema, the law is permissible provided that it is done without causing excessive harm to animals. Meanwhile, according to Ulama Persis, the law is that it should not be haram, because there are concerns that it could potentially torture animals and be contrary to Islamic principles. Keywords: NU Ulama, Persis Ulama, Art of Stunt Fighting